Z and E rotamers of N‐formyl‐1‐bromo‐4‐hydroxy‐3‐methoxymorphinan‐6‐one and their interconversion as studied by 1H/13C NMR spectroscopy and quantum chemical calculations. (11th December 2012) - Sulima, Agnieszka; Cheng, Kejun; Jacobson, Arthur E.; Rice, Kenner C.; Gawrisch, Klaus; Lee, Yong‐Sok
<x xml:space="preserve">Abstract</x> N‐Formyl‐1‐bromo‐4‐hydroxy‐3‐methoxymorphinan‐6‐one (compound 2), an important intermediate in the NIH Opiate Total Synthesis, presumably exists as a mixture of two rotamers (Z and E) in both CHCl3 and DMSO at room temperature due to the hindered rotation of its N‐C18 bond in the amide moiety. By comparing the experimental 1H and 13C chemical shifts of a single rotamer and the mixture of compound 2 in CDCl3 with the calculated chemical shifts of the geometry optimized Z and E rotamers utilizing density functional theory, the crystalline rotamer of compound 2 was characterized as having the E configuration. The energy barrier between the two rotamers was also determined with the temperature dependence of 1H and 13C NMR coalescence experiments, and then compared with that from the reaction path for the interconversion of the two rotamers calculated at the level of B3LYP/6‐31G*. Detailed geometry of the ground state and the transition states of both rotamers are given and discussed. Copyright © 2012 This article is a US Government work and is in the public domain in the USA.